Kerr Medium for Change of Light Frequency With Saw-Tooth Intensity Pattern Accommodating Multi-Passing Technique - Chatterjee, A; Mukhopadhyay, S (International Journal of Computer Sciences and Engineering, 2025)
Optical Kerr materials are strongly recommended for optical self-focusing and defocusing, optical switching activities and optical signal processing. The refractive index of Kerr medium depends on the intensity of applied light pulse passing through it. Kerr medium can be used in frequency conversion if signal having time dependent intensity pattern is passed through such a medium. Earlier this Kerr material was successfully used to convert the frequency of the applied light using a saw-tooth type of intensity varying signal. The shift of frequency can be enhanced by sending the output modulated wave from Kerr medium again to the input of the same medium. Greater amount of frequency shift can be achieved by increasing the number of passing of the light wave through the Kerr medium. Here in this paper the authors propose a method of using Kerr medium for change of light frequency with saw-tooth intensity pattern accommodating the multi-passing technique.